Novel Therapeutic Strategies for Ovarian Cancer Stem Cells - Terraneo, Nastassja; Jacob, Francis; Dubrovska, Anna; Grünberg, Jürgen (Frontiers in Oncology, 2020)
Ovarian cancer (OC) is one of the most lethal gynecologic malignancies. Due to the lack of specific symptoms and screening methods, this disease is usually diagnosed only at advanced and metastatic stage. The gold-standard treatment for OC patients consists in debulking surgery followed by taxane and platinum-based chemotherapy. Most patients show complete clinical remission after first-line therapy but the majority of them ultimately relapse, developing radio- and chemoresistant tumors. It is now evident that the cause of recurrence and poor therapy efficacy is the presence of small populations of cancer stem cells (CSCs). These cells are usually resistant against conventional cancer therapies and for this reason, effective targeted therapies for the complete eradication of CSCs are urgently needed. In this review article, we highlight the mechanisms of CSC therapy resistance, epithelial-to-mesenchymal transition, stemness and novel therapeutic strategies for ovarian CSCs.